2016
DOI: 10.5935/1806-6690.20160022
|View full text |Cite
|
Sign up to set email alerts
|

Steers production in integrated crop-livestock systems: pasture management under different sward heights

Abstract: -The aim of this study was to evaluate the effects of different grazing intensities on forage production and animal performance of yearling steers kept under permanent grazing in an integrated crop-livestock system. The treatments consisted of areas with sward heights of 10; 20; 30 and 40 cm, and one treatment with no grazing. The pastures were of bristle oat (Avena strigosa Schreb.) and annual ryegrass (Lolium multiflorum Lam.) following soybean (Glycine max (L.) Merr.). The variables forage mass, forage allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…Pasture productivity is affected by grazing intensity (Figure ). Increased grazing intensities reduced sward surface heights and average herbage masses, corroborating previous research (Carvalho et al., ; Wesp et al., ). These authors suggested the sward height as a practical management tool in establishing goals for pasture structure and animal production.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pasture productivity is affected by grazing intensity (Figure ). Increased grazing intensities reduced sward surface heights and average herbage masses, corroborating previous research (Carvalho et al., ; Wesp et al., ). These authors suggested the sward height as a practical management tool in establishing goals for pasture structure and animal production.…”
Section: Discussionsupporting
confidence: 89%
“…This should result in higher animal performance when compared to intensive grazing, as reported by Wesp et al. (), who observed higher animal weight gains in pastures managed between 20 and 30 cm of sward height.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These authors recommended a constant of approximately 2,000 kg ha -1 of cover crop biomass for no-till systems. In contrast, the values found in our study were lower (3,800 kg of DM ha -1 ) than those recommended by Wesp et al (2016) to overcome the effect of animal trampling on soil physical characteristics. The greatest herbage mass in the final period (159-187 DAS) of pasture usage was the result of the prolonged vegetative cycle of these species; however, this was associated with an increase in the stem and dead material proportions ( Figure 3).…”
Section: Herbage Mass and Plant-part Compositioncontrasting
confidence: 98%
“…Benefits of SPS include the delivery of more ecosystem services from different categories, such as provisioning, regulating, supporting, and cultural services (Dubeux et al., 2017a). Grazing animals in SPSs improve nutrient cycling because of faster nutrient turnover and soil organic C (Wesp et al., 2016), increasing soil C stock (Aryal, Gómez‐Gonzalez, Hernández‐Nuriasmú, & Morales‐Ruiz, 2019), and leading to a more efficient land use (Dubeux et al., 2017b). Further benefits include decreased greenhouse gas emissions, such as nitrous oxide and methane (Foley et al., 2011; Gibbs et al., 2010), and the additional source of income to producers coming from livestock (Esperschuetz et al., 2017).…”
Section: Introductionmentioning
confidence: 99%